The Implementation of Rasulullah SAW Leadership in Education: - Jabar, Padli Abdul; Ansari, Nia Rahmawati; Haryanti, Erni (Jurnal Manajemen Pendidikan, 2024)
Background The leadership of the Rasulullah SAW is one of the leadership models that is often implemented by all Muslims. Without a leader, an organization would only b e a group of people and equipment without direction In Islam, leadership is of great concern, this is explained in a hadith that requires that each group have a lead er, even in small numbers. Purpose This study aims to find out a bout the leadership of the Rasulullah SAW that is often implemented in educational leadership Design/method/approach This method research used a qualitative descriptive approach. And the data collection technique in this study uses library techniques (Research Library) such as journals, books, and websites that are used as references. Results The Results show that The application of Rasulullah SAW leadership In Educational Leadership The research results identify the leadership of the Prophet Muhammad SAW as applied in educational leadership through: honesty, trustworthiness, justice, communicativeness, consultation, and exemplary behavior. These points are the keys to carrying the trust of leadership. From the many leadership models, it shows that the success of a leader lies in their ability to adapt to situations, motivate, and empower the people they lead. Contribution/value             This concept illustrates how the leadership of Rasulullah SAW in educational leadership shapes a character of leadership that is honest, trustworthy, and reliable, serving as a role model for all of humanity. This should be a crucial point for future educational leadership to create an effective and efficient environment.